2014
DOI: 10.1186/1750-9378-9-9
|View full text |Cite
|
Sign up to set email alerts
|

Epstein Barr virus: a prime candidate of breast cancer aetiology in Sudanese patients

Abstract: Breast cancer is the commonest cancer in Sudanese women. Reported genetic alterations in the form of mutations in tumor suppressors are low in frequencies and could not explain the peculiarities of the diseases including its focal nature. Potential contributors disease aetiology include oncogenic viruses such as Epstein-Barr virus (EBV), an established culprit of nasopharyngeal carcinoma, one of the most frequent cancers in Sudan.In this study, DNA was extracted from malignant tissue samples and healthy tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 27 publications
(22 reference statements)
5
56
1
1
Order By: Relevance
“…This result is below the values reported in other studies conducted at a global level, which range from 21-55% of EBV DNA positivity, depending on the type of technique employed for viral DNA detection 4,19,40 . In works using some type of PCR, as in our study, low infection rates were detected, as in the trial by Xue, et al in 2003, who, using BZLF1 gene-specific reverse transcriptase PCR, detected viral DNA in 17% of breast cancer cases, and the work by Yahia, in 2014, who detected 11% of EBV DNA positivity in breast cancer cases using PCR with EBNA-1 gene-specific primers 41,42 . In Latin America, very few studies have assessed the presence of EBV in breast cancer, and have reported a rate of infection ranging from 6-31% 31,43 .…”
Section: Discussionsupporting
confidence: 69%
“…This result is below the values reported in other studies conducted at a global level, which range from 21-55% of EBV DNA positivity, depending on the type of technique employed for viral DNA detection 4,19,40 . In works using some type of PCR, as in our study, low infection rates were detected, as in the trial by Xue, et al in 2003, who, using BZLF1 gene-specific reverse transcriptase PCR, detected viral DNA in 17% of breast cancer cases, and the work by Yahia, in 2014, who detected 11% of EBV DNA positivity in breast cancer cases using PCR with EBNA-1 gene-specific primers 41,42 . In Latin America, very few studies have assessed the presence of EBV in breast cancer, and have reported a rate of infection ranging from 6-31% 31,43 .…”
Section: Discussionsupporting
confidence: 69%
“…2016; 11(3):e34806. (11,18,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53). Table 1 shows a summary of the EBV-DNA positive subjects according to nationality, types of sample, and kinds of control tissue in the 20 selected studies.…”
Section: Resultsmentioning
confidence: 99%
“…EBV genomic sequences were detected in a large fraction of tested Sudanese breast cancer specimens, suggesting an association between EBV and breast carcinoma in Sudanese patients [71].…”
Section: Breast Cancer Genetics In Sudanmentioning
confidence: 97%